2022
DOI: 10.29133/yyutbd.1073555
|View full text |Cite
|
Sign up to set email alerts
|

Determination of The Effect of Salicylic Acid Application on Salinity Stress at Germination Stage of Bread Wheat

Abstract: Under changing climate, abiotic stresses especially salinity have posed serious threats to modern crop production systems of staple crops and chemo-priming with salicylic acid offers a promising remedy. The present study aimed at ameliorating the adverse effects of salt stress through optimization of salicylic acid (SA) for two bread wheat genotypes (DZ17-1 and Empire Plus). The trial was comprised of chemo-priming with different SA levels including 0, 0.5, and 1 mM applied to the seeds of bread wheat genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Similarly, Haghighia et al (2020) also found that exogenous amino acid implementation given to squash seedlings significantly increased amino acid, protein, and proline content in comparison to the control group. Enzymatic molecules of defense mechanisms such as CAT, POD, and SOD suppress ROS production in plants under stress conditions or they scavenge these compounds from the cells (Ikbal et al, 2019;Yılmaz et al, 2022). In the present study, CAT activity was stimulated by 500GLU and 50NaCl +250GLU, 50NaCl-500GLU, and POD activity decreased in high NaCl and NaCl + GLU (Figure 2B, 2C).…”
Section: Effects Of Nacl and Glu Treatments On The Bioactive Chemical...supporting
confidence: 50%
See 3 more Smart Citations
“…Similarly, Haghighia et al (2020) also found that exogenous amino acid implementation given to squash seedlings significantly increased amino acid, protein, and proline content in comparison to the control group. Enzymatic molecules of defense mechanisms such as CAT, POD, and SOD suppress ROS production in plants under stress conditions or they scavenge these compounds from the cells (Ikbal et al, 2019;Yılmaz et al, 2022). In the present study, CAT activity was stimulated by 500GLU and 50NaCl +250GLU, 50NaCl-500GLU, and POD activity decreased in high NaCl and NaCl + GLU (Figure 2B, 2C).…”
Section: Effects Of Nacl and Glu Treatments On The Bioactive Chemical...supporting
confidence: 50%
“…The L-GLU concentration applied in the study was determined by a preliminary study. For the GLU concentration, it was selected by considering the germination capacity of the seeds which caused an average 50% increase, while the NaCl concentrations were determined by considering the germination capacity that increased by more than 50% and caused more than 50% inhibition (Sadak et al, 2015;Yılmaz et al, 2022).…”
Section: Arrangement Of Experimental Design Of the Studymentioning
confidence: 99%
See 2 more Smart Citations